Semiconducting Supramolecular Organic Frameworks Assembled from a Near-Infrared Fluorescent Macrocyclic Probe and Fullerenes - Kaur, Ramandeep; Sen, Sajal; Larsen, Mads Christian; Tavares, Luciana; Kjelstrup-Hansen, Jakob; Ishida, Masatoshi; Zieleniewska, Anna; Lynch, Vincent M.; Bahring, Steffen; Guldi, Dirk Michael; Sessler, Jonathan L.; Jana, Atanu (Journal of the American Chemical Society, 2020)
We report here a new extended tetrathiafulvalene (exTTF)-porphyrin scaffold, 2, that acts as a ball-and-socket receptor for C60 and C70. Supramolecular interactions between 2 and these fullerenes serve to stabilize 3D supramolecular organic frameworks (SOFs) in the solid state formally comprising peapod-like linear assemblies. The SOFs prepared via self-assembly in this way act as "tunable functional materials", wherein the complementary geometry of the components and the choice of fullerene play crucial roles in defining the conductance properties. The highest electrical conductivity (σ = 1.3 × 10-8 S cm-1 at 298 K) was observed in the case of the C70-based SOF. In contrast, low conductivity was seen for the SOF based on pristine 2 (σ = 5.9 × 10-11 S cm-1 at 298 K). The conductivity seen for the C70-based SOF approaches that seen for other TTF-and fullerene-based supramolecular materials despite the fact that the present systems are metal-free and constructed entirely from neutral building blocks. Transient absorption spectroscopic measurements corroborated the formation of charge-transfer states (i.e., 2δ+/C60δ- and 2δ+/C70δ-, respectively) rather than fully charge separated states (i.e., 2•+/C60•- and 2•+/C70•-, respectively) both in solution (toluene and benzonitrile) and in the solid state at 298 K. Such findings are considered consistent with an ability to transfer charges effectively over long distances within the present SOFs, rather than, for example, the formation of energetically trapped ionic species.
CRIS-Team Scopus Importer:2020-07-24